Solvothermal synthesis and photocatalytic performance of Mn4+-doped anatase nanoplates with exposed {001} facets - Sofianos, Veronica; Tassi, M.; Psycharis, V.; Boukos, N.; Thanos, S.; Vaimakis, T.; Yu, J.; Trapalis, C. (Elsevier BV, 2015)
The photocatalytic activity of TiO2 and manganese doped TiO2 nanoplates with various manganese atomic percentages, in the range of 2-7%, was studied. The undoped and doped nanoplates with exposed {001} facets were produced by a solvothermal method. The crystal structure as well as the shape of the TiO2 and Mn4+/TiO2 anatase nanoparticles was determined with X-ray powder diffraction (XRD) and transmission electron microscopy (TEM). Both techniques revealed that the nanocrystals are in the form of plates. Moreover, the anisotropic peak broadening of the X-ray diffraction patterns was studied using the Rietveld refining method. Chemical analysis of the photocatalyst that was carried out with X-ray photoelectron spectroscopy (XPS) showed the presence of manganese ions in the TiO2 anatase matrix. The Density Functional Theory (DFT) calculations exhibited a decrease in the energy gap and an increase in the density of the electronic stated inside the gap for the doped TiO2. These observations were in agreement with the results of the UV-visible diffuse reflectance spectroscopy (DRS) that demonstrated an adsorption shift towards the visible region for the same samples. The photocatalytic activity of the synthesized catalysts was investigated by the photocatalytic oxidation of the gaseous nitric oxide (NO) and decomposition of the gaseous acetaldehyde (CH3CHO) under visible light irradiation. The optimal concentration of dopant that improves the photocatalytic activity of the nanoplates was determined. © 2014 Elsevier B.V.